MODELS OF SCHOLARSHIP TRAINING PROGRAMS FOR HIGHLY QUALIFIED PERSONNEL - V. L. Petrov; Yu. E. Babichev (Высшее образование в России)
The paper presents the universal models of learning trajectory and curriculum of scholarship training programs for research and teaching personnel of highly qualification. These models do not depend on the research area and the terms of learning. The authors propose guidelines how to fill up the Unit 1 with the disciplines (modules) and to determine the contents of pedagogical and research practical sessions on the basis ofprofessional standards. The paper also suggests the possible set of disciplines for State examination suitable for any area of training.